Supplementation of Vitamin C Reduces Blood Glucose and Improves Glycosylated Hemoglobin in Type 2 Diabetes Mellitus: A Randomized, Double-Blind Study - Ganesh N. Dakhale; Harshal V. Chaudhari; Meena Shrivastava (Hindawi Limited, 2011)
No study has ever examined the effect of vitamin C with metformin on fasting (FBS) and postmeal blood glucose (PMBG) as well as glycosylated hemoglobin (HbA1c) in the treatment of type 2 diabetes mellitus (DM). The goal was to examine the effect of oral vitamin C with metformin on FBS, PMBG, HbA1c, and plasma ascorbic acid level (PAA) with type 2 DM. Seventy patients with type 2 DM participated in a prospective, double-blind, placebo-controlled, 12-week study. The patients with type 2 DM were divided randomly into placebo and vitamin C group of 35 each. Both groups received the treatment for twelve weeks. Decreased PAA levels were found in patients with type 2 diabetes mellitus. This level was reversed significantly after treatment with vitamin C along with metformin compared to placebo with metformin. FBS, PMBG, and HbA1c levels showed significant improvement after 12 weeks of treatment with vitamin C. In conclusion, oral supplementation of vitamin C with metformin reverses ascorbic acid levels, reduces FBS, PMBG, and improves HbA1c. Hence, both the drugs in combination may be used in the treatment of type 2 DM to maintain good glycemic control.